Análise da biocompatibilidade de cones de biovidro e biovitrocerâmico (Biosilicato®) em cavidade eviscerada de coelho - Brandão, Simone Milani [UNESP]; Schellini, Silvana Artioli [UNESP]; Padovani, Carlos Roberto [UNESP]; Peitl, Oscar; Hashimoto, Emerson [UNESP] (Revista Brasileira de Oftalmologia, 2013)
Objective: To evaluate bioglass, bioglassceramic biocompatibility in rabbit's eviscerated cavities. Methods: Forty- five rabbits were submitted to right eye evisceration, followed by the inclusion of bioglass and bioglassceramic I e II prosthesis in the escleral cavity. The animals were sacrificed at seven, 90 and 180 days after surgery. The animals had daily clinical exam; biochemical exam, histological analysis and morphometric evaluation. Results: The animals stayed healthy during the expriment, with good cone integration to the host tissue. None cone extrusion were observed. Histologically, it was observed pseudocapsule formation around the cones and the inflammatory reaction was higher at M1, getting progressively lower while getting at M3, being the lowest in rabbits which received bioglass cones (GA) than at any other groups. Conclusion: Bioglass and bioglassceramic I e II cones can be useful to repair anophthalmic cavity.
Biocompatibility analisys of Bioglass® 45S5 and Biosilicate® cone in rabbit eviscerated cavity
Keywords: Anophthalmic cavity; Biocompatible materials; Experimental; Implants; Rabbits